Pathology Associated with White Spot Virus (WSV) Infection in Wild Broodstock of Tiger Prawns (Penaeus monodon) - Beng Chu Kua; Noraziah Mat Rashid (Tropical Life Sciences Research, 2012)
A total of six wild broodstocks of tiger prawns, Penaeus monodon, were found positive for White Spot Virus (WSV) with an IQ2000 detection kit. Using histopathology, the intranuclear inclusion of haemocyte due to WSV infection was observed in the epithelium cells of the antennal gland, stomach and gills. This result confirmed that the wild broodstocks were positive with WSV without showing any white spot. Additionally, histopathological examination also revealed an accumulation of haemocytes around the hepatopancreatic tubules resulting from bacterial infection. Encapsulation and nodule formation, as well as related necrosis, were also observed around the hepatopancreatic tubules infected with a metazoan parasite. Encysted tylocephalum larval cestodes were observed in the hepatopancreas, with haemocytic aggregation being observed around the infected tubules. These findings showed some bacterial and parasitic infections which, in addition to the viral infection itself, could contribute to the 80% mortality rate in wild broodstocks infected with WSV. Sebanyak enam induk liar udang harimau, Penaeus monodon, didapati positif Virus Bintik Putih (WSV) dengan kit pengesanan IQ2000. Histopatologi pada induk udang tersebut menunjukkan jangkitan WSV dengan kehadiran sel hematosit dalam nukleus pada sel-sel epitelium kelenjar antennal, perut dan insang. Induk liar positif dengan WSV ini tidak menunjukkan tanda-tanda penyakit seperti bintik-bintik putih seperti kebiasaan jangkitan WSV. Histopatologi menunjukkan kehadiran hematosit yang terkumpul di sekitar tubul hepatopankreatik akibat jangkitan bakteria. Pengurungan bakteria, pembentukan nodul dan nekrosis juga dikesan pada tubul hepatopankreatik yang turut dijangkiti oleh larva cestoda. Larva Tylocephalum dikesan dalam bentuk kurungan pada organ hepatopankreas dengan dikelilingi oleh sel hematosit. Penemuan ini menunjukkan jangkitan bakteria dan parasit, sebagai tambahan kepada jangkitan virus itu sendiri, boleh menyumbang kepada 80% kadar kematian pada liar induk yang positif dengan WSV.